Bond Liquidity Premia - Fontaine, Jean-Sébastien; Garcia, René (Review of Financial Studies, 2012)
Recent asset pricing models of limits to arbitrage emphasize the role of funding conditions faced by financial intermediaries. In the US, the repo market is the key funding market. Then, the premium of on-the-run U.S. Treasury bonds should share a common component with risk premia in other markets. This observation leads to the following identification strategy. We measure the value of funding liquidity from the cross-section of on-the-run premia by adding a liquidity factor to an arbitrage-free term structure model. As predicted, we find that funding liquidity explains the cross-section of risk premia. An increase in the value of liquidity predicts lower risk premia for on-the-run and off-the-run bonds but higher risk premia on LIBOR loans, swap contracts and corporate bonds. Moreover, the impact is large and pervasive through crisis and normal times. We check the interpretation of the liquidity factor. It varies with transaction costs, S&P500 valuation ratios and aggregate uncertainty. More importantly, the liquidity factor varies with narrow measures of monetary aggregates and measures of bank reserves. Overall, the results suggest that different securities serve, in part, and to varying degrees, to fulfill investors' uncertain future needs for cash depending on the ability of intermediaries to provide immediacy.